ANALISIS TENTANG NILAI – NILAI PANCASILA YANG TERDAPAT DALAM KESENIAN RARAK GODANG KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Gushailen Putra Kamil; Gimin Gimin; Hambali Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was motivated by values of Pancasila contained in art rarak Godang Hilir Subdistrict Kuantan Kuantan Singingi. The problems in this study is whether there are values of Pancasila contained in rarak Art Godang Hilir Subdistrict Kuantan Kuantan Singingi? ". This study aims to determine the values of Pancasila contained in art rarak Godang Hilir Subdistrict Kuantan Kuantan Singingi ". This research was conducted in the District of Kuantan Hilir Regency Kuantan Singingi ". This research was conducted in the District of Kuantan Hilir Regency Kuantan Singingi in May 2016. This study is a qualitative descriptive study, the population in this study is the whole society Hilir Subdistrict Kuantan Kuantan Singingi. The sample in this study were drawn based on the technique of "purposive sampling". Data collection instruments, namely by questionnaires and interviews. The results of this study with the results with the percentage of "Yes" ie 66.80%, are in the range of 50.01% -100% = there, so it can be concluded that there are values of Pancasila in the arts rarak GodangKeywords : Values Pancasila art Rarak Godang